COVID‐19 lockdown disrupts support networks integral to maintaining foot health: a mixed‐methods study - Lindsey Cherry; Lucy Gates; David Culliford; Karen Walker‐Bone; Mari Carmen Portillo (Journal of Foot and Ankle Research, 2021)
Abstract Background In response to the COVID‐19 pandemic, populations were advised to remain at home to control viral spread. Government‐mandated restrictions on free movement affected individuals' engagement with physical activity, with reported increases leading to biopsychosocial health benefits and conversely increased sedentary behaviour leading to poorer health. Good foot health is key to enabling physical activity and maximal participation in activities of occupation and daily living. Methods A population‐based cross‐sectional study was performed, using a web‐based platform. Quantitative and qualitative data were captured through responses to closed and open survey questions. Anybody with a foot health condition was eligible to participate in the online survey. Links were sent through professional networks, support groups and charities, using a snowball strategy to maximise participation. Results Two hundred fifty‐five respondents completed the survey. Most (n = 193, 75.69%) reported an ongoing foot pain or problem that had been present for 4 weeks or longer, whilst 49 respondents (19.22%) noted a new pain or problem. Pain was the most frequently reported symptom (n = 139, 54.51%), whilst change in appearance of the foot was also commonly reported (n = 122, 47.84%), often alongside the observable presence of swelling. Musculoskeletal foot symptoms were frequently reported (n = 123, 48%), and were significantly associated with reported reduced physical activity (X2 = 6.61, p = 0.010). Following qualitative analysis five themes and 11 subthemes emerged, informed by 49 independent codes. A central theme of lockdown disrupting support networks, both formal (healthcare providers) and informal (friends or family members) emerged. The 5 sub‐themes were: 1. foot pain is a constant companion, 2. self‐care, 3. ‘cope or crumble’ scenarios, 4. future intent to access healthcare and 5. reduced ability to undertake physical activity. Conclusions Pain was the most frequently reported foot problem during COVID‐19 lockdown restriction. Lockdown restrictions disrupted support networks integral to maintaining foot health. Poor foot health impacted people's ability to remain physically active. Complaints previously considered relatively ‘minor’ such as support for skin and nail care, were found to be exacerbated by restricted support networks, leading to greater negative impact.